Influence of CYP2D6 genetics on opioid kinetics, metabolism and response - Mikus, Gerd; Weiß, Johanna (Current pharmacogenomics, 2005)
Pharmacogenetics does seem to play a key role in the use of so-called weak opioids. It has been shown for codeine, dihydrocodeine, oxycodone and hydrocodone, that their O-demethylation in the 3-position results in metabolites which have much stronger μ-receptor binding. These opioids may therefore exert their pharmacological actions predominantly through their O-demethylated metabolites. However, this metabolic step is under genetic control of the polymorphic cytochrome P450 2D6 isozyme (CYP2D6). Poor metabolisers of CYP2D6 (∼10% of the Caucasian population) do not express this enzyme and hence can only form trace amounts of the O-demethylated metabolites of these four opioids. This might put these persons on risk of reduced or even abolished analgesic effects when given these weak opioids. From this point of view there are two major issues why weak opioids cannot wholeheartedly be recommended: large interindividual variability of the analgesic effect due to CYP2D6 polymorphism and 10% of patients with no benefit from these drugs. On the other hand it might be advantageous to use the O-demethylated metabolites morphine, oxymorphone and hydromorphone which are all strong opioids and have a smaller interindividual variability of the opioid effects. Instead of using weak opioids, small doses and controlled release formulations of strong opioids might be the future way to in analgesic therapy despite the fear of addiction and bureaucratic efforts involved with these compounds.
Gesehen am 10.09.2021